Digitalization of village based on information technology through developing BUMDes MSMEs website and logo - Kristiyanti, Dinar Ajeng; Alexandra, Yoanita; Situmorang, Ringkar; Athira, Reva Fakhrana; William, Juanito Arvin (University of Islam Malang, 2024)
The development of technology has transformed the global economic landscape, including in the realm of Micro, Small, and Medium Enterprises (MSMEs). However, MSME actors in various villages and regions often still have limitations in understanding the importance of digitalization, especially in utilizing technology to promote their products. Therefore, this Community Engagement activity is initiated with the main goal of creating and disseminating understanding about the importance of implementing a profile website, financial management application, and logo in efforts to increase visibility and sales of products for MSME actors in the Serdang Tirta Kencana Village-Owned Enterprises (BUMDes) in Tangerang, Indonesia. The implementation method is based on Community-Based Participatory Research Program (CBPR) with the following stages are location survey, website and logo creation, socialization, and evaluation. Through close collaboration with local stakeholders from BUMDes Serdang Tirta Kencana, this activity has successfully empowered MSME actors with a strong visual identity and significant digital presence. The result is a 95% increase in the skills of MSME actors in BUMDes Serdang Tirta Kencana. It is hoped that through this activity, MSME actors can become competitive and have a positive impact on local economic growth and community empowerment